The Effects of the SPACE Learning Model on Learning Achievement and Innovation & Learning Skills in Higher Education - Napatcha Pradubthong; Sirirat Petsangsri; Paitoon Pimdee (My University, 2018)
Abstract The objectives of this research were to develop a flipped classroom design, and to investigate the learning achievements and the innovation and learning skills of undergraduate students who had registered on a software engineering course which used the flipped classroom design. The suitability of flipped classroom lesson plans was evaluated by nine experts. The sample comprised 63 undergraduate students –33 students in the experimental group and 30 students in the control group - who had registered on the software engineering course in the first semester in 2017. The samples were selected by using the cluster random sampling method. The research instruments used were: (1) the flipped classroom lesson plans; (2) a multiple-choice learning achievement test, and (3) an evaluation form for learning and innovation skills rubric scoring. Mean (x̄), standard deviation, and one-way MANOVA were used to analyze data. The results found that: 1) The suitability of the flipped classroom lesson plans was at a high level (x̄ = 4.45, SD = 0.73). 2)The learning achievement results and the innovation and learning skills of undergraduate students who studied software engineering by the use of the flipped classroom design were higher than those of undergraduate students in a normal classroom, with a level of significance of 0.05.
Keywords: Rubric; Flipped Classroom; Innovative Teaching Methods